Biomedical Engineering 2010
DOI: 10.2316/p.2010.723-141
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Tracking System for Neurovascular Interventions

Abstract: Electromagnetic tracking systems (EMTS) are widely used in a computer-assisted surgery, motion capture, kinematic studies and military applications. The main application in the medical domain represents minimal invasive surgery. For this purpose, the EMTS systems are integrated into the surgery device, i.e. needle, endoscope or catheter supporting tracking of this device within the human body without X-ray radiation. However, in neurovascular interventions this technique hardly could be applied so far. This is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Many studies assessing EM tracking systems for CAI can be found in the literature, e.g., [3,6,7,15,19,25,36,39,45,51,59,60,61,66,74,82,83,86,89,102,120,122,152,154,159,165,169,170,172,196,202,206,207]. However, in many cases, the results of these studies are not comparable because different measurement protocols and evaluation methods were used.…”
Section: B Study Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies assessing EM tracking systems for CAI can be found in the literature, e.g., [3,6,7,15,19,25,36,39,45,51,59,60,61,66,74,82,83,86,89,102,120,122,152,154,159,165,169,170,172,196,202,206,207]. However, in many cases, the results of these studies are not comparable because different measurement protocols and evaluation methods were used.…”
Section: B Study Resultsmentioning
confidence: 99%
“…Phantoms of different anatomical structures such as the abdomen [199], the skull [165] and vessels [15] have been used. Some assessments have even been performed during actual interventions inside the human body [86,172].…”
Section: Assessments In Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation